Factors Affecting The Collaborative Relationships in Tourism Supply Chain - Trang Thi Huyen Tran (International Journal for Applied Information Management, 2021)
Structural Equation Modeling was employed to examine the influence of several factors: trust, commitment, personal relationship, application of information technology in the chain, customer orientation policy, asset specificity and behavioral uncertainty to the collaborative relationships between travel companies and their suppliers in the tourism supply chain. The results indicate that the first four factors have direct and positive impacts on this collaborative relationship. Furthermore, the study also confirmed the nexus between trust as well as customer orientation policy and the commitment among members in tourism supply chain.